Microsatellites for Oenothera gayleana and O. hartwegii subsp. filifolia (Onagraceae), and their utility in section Calylophus1. (9th February 2016) - Lewis, Emily M.; Fant, Jeremie B.; Moore, Michael J.; Hastings, Amy P.; Larson, Erica L.; Agrawal, Anurag A.; Skogen, Krissa A.
Abstract : Premise of the study: Eleven nuclear and four plastid microsatellite markers were screened for two gypsum endemic species, Oenothera gayleana and O. hartwegii subsp. filifolia, and tested for cross‐amplification in the remaining 11 taxa within Oenothera sect. Calylophus (Onagraceae). Methods and Results: Microsatellite markers were tested in two to three populations spanning the ranges of both O. gayleana and O. hartwegii subsp. filifolia . The nuclear microsatellite loci consisted of both di‐ and trinucleotide repeats with one to 17 alleles per population. Several loci showed significant deviation from Hardy–Weinberg equilibrium, which may be evidence of chromosomal rings. The plastid microsatellite markers identified one to seven haplotypes per population. The transferability of these markers was confirmed in all 11 taxa within Oenothera sect. Calylophus . Conclusions: The microsatellite loci characterized here are the first developed and tested in Oenothera sect. Calylophus . These markers will be used to assess whether pollinator foraging distance influences population genetic parameters in predictable ways.